Upaya Pencegahan Serangan Panik Saat Pandemi Covid 19 Melalui Anxiety First Aid (AFA), Dan Edukasi - Febriana Sartika Sari; Wahyuningsih Safitri; Maria Wisnu Kanita; Intan Maharani S. Batubara (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: The pandemic of COVID 19 has impact on many field include mental health. People experience fear, anxiety, and even panic attacks. Anxiety will cause many negative effects. Handling anxiety quickly can be done by providing Anxiety First Aid . The purpose of the research is to increase the citizen level of knowledge and skill about Anxiety First Aid and adaptive coping in COVID 19 pandemic. Methods: Activities carried out by three main activities such as screening of panic incident, providing Anxiety First Aid (AFA) training, and education about adaptive coping. Respondents involved were 21 residents of Bonoroto Plesungan Karanganyar Central Java. Results: There is a resident who has panic incident history. The knowledge and skill of residents increase after giving training and education. The pre-test showed that the majority of the respondents had bad knowledge (90,47% or 19 respondents) and bad skill (100% or 21 respondents). The post-test showed that the majority of the respondents had good knowledge (86% or 18 respondents) and good skill (86% or 18 respondents). Conclusion: Adaptive coping and Anxiety First Aid are highly recommended to prevent panic attacks during COVID 19 pandemic.